Sex-related differences in patients presenting with heart failure–related cardiogenic shock - Sundermeyer, Jonas; Kellner, Caroline; Beer, Benedikt N.; Besch, Lisa; Dettling, Angela; Bertoldi, Letizia Fausta; Blankenberg, Stefan; Dauw, Jeroen; Dindane, Zouhir; Eckner, Dennis; Eitel, Ingo; Graf, Tobias; et al. (Clinical Research in Cardiology, 2024)
Background: Heart failure–related cardiogenic shock (HF-CS) accounts for a significant proportion of all CS cases. Nevertheless, there is a lack of evidence on sex-related differences in HF-CS, especially regarding use of treatment and mortality risk in women vs. men. This study aimed to investigate potential differences in clinical presentation, use of treatments, and mortality between women and men with HF-CS. Methods: In this international observational study, patients with HF-CS (without acute myocardial infarction) from 16 tertiary-care centers in five countries were enrolled between 2010 and 2021. Logistic and Cox regression models were used to assess differences in clinical presentation, use of treatments, and 30-day mortality in women vs. men with HF-CS. Results: N = 1030 patients with HF-CS were analyzed, of whom 290 (28.2%) were women. Compared to men, women were more likely to be older, less likely to have a known history of heart failure or cardiovascular risk factors, and lower rates of highly depressed left ventricular ejection fraction and renal dysfunction. Nevertheless, CS severity as well as use of treatments were comparable, and female sex was not independently associated with 30-day mortality (53.0% vs. 50.8%; adjusted HR 0.94, 95% CI 0.75–1.19). Conclusions: In this large HF-CS registry, sex disparities in risk factors and clinical presentation were observed. Despite these differences, the use of treatments was comparable, and both sexes exhibited similarly high mortality rates. Further research is necessary to evaluate if sex-tailored treatment, accounting for the differences in cardiovascular risk factors and clinical presentation, might improve outcomes in HF-CS. Graphical abstract: Sex-related differences in clinical characteristics, shock severity, and mortality in patients with heart failure–related cardiogenic shock. Summary for the main study findings. AMI, acute myocardial infarction; CI, confidence interval; HF-CS, heart failure–related cardiogenic shock; LVEF, left ventricular ejection fraction; MCS, mechanical circulatory support; SCAI, Society for Cardiovascular Angiography & Interventions. (Figure presented.).
CRIS-Team Scopus Importer:2024-03-29
Keywords: Cardiogenic shock; Gender differences; Heart failure; Sex disparities; Women in heart failure